The use of an image analyser for dimensional quantification in ultrasonic images - CHIVERS, Robert C.; DUDLEY, Henry J. W. (Archives of Acoustics, 1980)
The use of a sophisticated commercially available image analyser is described in the context of obtaining numerical geometrical data from ultraSonic visualization systems. As an example of its value, its application to the ultrasonic foetal monitoring is discussed. The main features are light pen selection, with immediate display and numerical analysis. Whereas the instrument is too sophisticated for routine use it could be invaluable in ascertaining the design specification of a simpler purpose-built system for incorporation into ultrasonic visualization equipment.